Evaluating The Performance of Islamic Banks Compared to The Performance of Traditional Banks Using "CAMELS" Model – Case Study of “Al-Rajhi Bank” and “the Saudi French Bank” During The Period (2015-2019) - mekatel, hemza; bounihi, meriem (Journal of Research in Finance and Accounting, 2021)
This study aims to highlight an important topic in banking activity, which is the evaluation of banks performance using the “CAMELS” model, where we used a descriptive analytical approach with an applied study of two banks, one is Islamic “Al Rajhi Bank”, and the other is traditional “the Saudi French Bank”, during the period (2015-2019(. The results indicate that the two banks have a strong solvency, a good profit, and a sound management that classify them in the first place which reflects the extent of safety that characterizes their work. We have also found that “Al Rajhi Bank” has achieved strong results that have made it superior to the traditional bank in all aspects, especially in capital adequacy).